1986
DOI: 10.1177/000456328602300608
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine Concentrations in Dialysed and Undialysed Patients with Chronic Renal Insufficiency

Abstract: SUMMARY.Free carnitine, acylcarnitine and total carnitine serum concentrations have been measured in chronic renal insufficiency patients under conservative treatment, in patients under regular haemodialysis treatment and in healthy controls. In the undialysed patients the levels of free camitine, acylcamitine and total carnitine were all clearly higher than those of the control group. The free carnitine and total carnitine levels of undialysed subjects were also higher than in regularly haemodialysed patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 24 publications
1
29
0
1
Order By: Relevance
“…HD is of particular note because it induces a substantial loss of carnitine from the skeletal and cardiac muscle. The typical plasma carnitine profiles in patients on chronic dialysis, as compared with the normal controls, show decreased FC, normal or subnormal TC [28,29], and significantly elevated AC/FC ratio, corresponding to the current data. The previous study showed that L-carnitine deficiency progresses with time on dialysis [10].…”
Section: Discussionsupporting
confidence: 84%
“…HD is of particular note because it induces a substantial loss of carnitine from the skeletal and cardiac muscle. The typical plasma carnitine profiles in patients on chronic dialysis, as compared with the normal controls, show decreased FC, normal or subnormal TC [28,29], and significantly elevated AC/FC ratio, corresponding to the current data. The previous study showed that L-carnitine deficiency progresses with time on dialysis [10].…”
Section: Discussionsupporting
confidence: 84%
“…[76] Regarding vitamin C, it functions as a cofactor for biosynthesis of carnitine, [77,78] and it exerts a protective role against the peroxidative damage through its lipid-lowering effect. [79] Carnitine itself has antioxidant action and a strong inhibitory effect on free radical production, [80,81] and it exerts thiol and methionine-sparing activity. [82] Furthermore, recent data showed that L-carnitine treatment is able to modify some particular aspects of the inflammatory status characterizing CRF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Carnitine deficiency can develop in ESRD patients after HD is instituted [2, 3, 7, 38]because of dialytic loss [2], decreased dietary intake [4]and decreased endogenous biosynthesis [3]. Ratios of acyl/free carnitine may also become abnormal [24].…”
Section: Discussionmentioning
confidence: 99%